Fe Foam-Supported FeS2–MoS2 Electrocatalyst for N2 Reduction under Ambient Conditions - Yang, Mengle; Jin, Zhongxin; Wang, Chenglong; Cao, Xixian; Wang, Xinming; Ma, Huiyuan; Pang, Haijun; Tan, Lichao; Yang, Guixin (ACS applied materials & interfaces, 2021)
Highly efficient catalysts with enough selectivity and stability are essential for electrochemical nitrogen reduction reaction (e-NRR) that has been considered as a green and sustainable route for synthesis of NH3. In this work, a series of three-dimensional (3D) porous iron foam (abbreviated as IF) self-supported FeS2–MoS2 bimetallic hybrid materials, denoted as FeS2–MoS2@IF x , x = 100, 200, 300, and 400, were designed and synthesized and then directly used as the electrode for the NRR. Interestingly, the IF serving as a slow-releasing iron source together with polyoxomolybdates (NH4)6Mo7O24·4H2O as a Mo source were sulfurized in the presence of thiourea to form self-supported FeS2–MoS2 on IF (abbreviated as FeS2–MoS2@IF200) as an efficient electrocatalyst. Further material characterizations of FeS2–MoS2@IF200 show that flower cluster-like FeS2–MoS2 grows on the 3D skeleton of IF, consisting of interconnected and staggered nanosheets with mesoporous structures. The unique 3D porous structure of FeS2–MoS2@IF together with synergy and interface interactions of bimetallic sulfides would make FeS2–MoS2@IF possess favorable electron transfer tunnels and expose abundant intrinsic active sites in the e-NRR. It is confirmed that synthesized FeS2–MoS2@IF200 shows a remarkable NH3 production rate of 7.1 ×10–10 mol s–1 cm–2 at −0.5 V versus the reversible hydrogen electrode (vs RHE) and an optimal faradaic efficiency of 4.6% at −0.3 V (vs RHE) with outstanding electrochemical and structural stability.